Effect of texture characteristics on the high-cycle fatigue properties of a Ti-6Al-4V alloy. (6th August 2021) - Yang, Huanping; Yan, Wenbin; Zhuang, Wei; Wang, Yaomian
Abstract: A Ti-6Al-4V alloy was rolled at different temperatures and subsequently annealed to obtain fatigue samples with different texture characteristics. The samples were then subjected to tension-tension high-cycle fatigue (HCF) tests and the fracture morphology was observed to correlate the texture characteristics with the HCF properties. The results show that the texture intensity significantly affects the HCF strength for the equiaxed microstructure of Ti-6Al-4V alloys with an equivalent grain size and the same texture type; also, the HCF strength decreases with increasing texture intensity. The fracture morphology observation and Schmid factor calculation show that planar facets, which are a characteristic feature of crack initiation sites, are formed due to the strength mismatch caused by the inhomogeneous slip distribution favored either for prismatic or basal slip. The effect of the texture intensity on the HCF properties can be explained by the influence of the number of pile-up locations of 'soft' grains neighboring 'hard' grains in the typical Stroh model that elucidates the planar facet formation mechanism.